#8M women's strikes in Spain: following the unprecedented social mobilization through twitter. Issue 5 (4th July 2022) - Idoiaga Mondragon, Nahia; Berasategi Sancho, Naiara; Beloki Arizti, Nekane; Belasko Txertudi, Maitane
ABSTRACT: The first general women's strikes to demand gender equality in Spain took place on 8 March 2018 and 2019. Both calls were an amazing success, becoming world references for feminism. This research investigates how the strikes were dealt with through Twitter by a Collective Symbolic Coping (CSC) process. Discourses on Twitter were analysed on both years, 4, 384 tweets were selected and their content was analysed by lexical analysis. The results from 2018 indicated the CSC phases of 1) awareness; 2) divergence, where feminist demands and the role of men in the strike were debated; and 3) convergence, where the success of the strike was highlighted. However, in 2019 the feminists on Twitter were forced to cope with a great deal of trolling against them. This trolling was maintained in the awareness and divergence phases, making it difficult to reach a convergent discourse regarding the success of the strike. Moreover, the results also demonstrated that there was no reference hashtag in the strikes. It is concluded that discourse on social networks has become a key factor in feminist social mobilizations and that this feminist digital activism will be critical in the continued dissemination of the claims for gender equality in Spain.